Road salt emissions: A comparison of measurements and modelling using the NORTRIP road dust emission model. (September 2016) - Denby, B.R.; Ketzel, M.; Ellermann, T.; Stojiljkovic, A.; Kupiainen, K.; Niemi, J.V.; Norman, M.; Johansson, C.; Gustafsson, M.; Blomqvist, G.; Janhäll, S.; Sundvor, I.
Abstract: De-icing of road surfaces is necessary in many countries during winter to improve vehicle traction. Large amounts of salt, most often sodium chloride, are applied every year. Most of this salt is removed through drainage or traffic spray processes but a certain amount may be suspended, after drying of the road surface, into the air and will contribute to the concentration of particulate matter. Though some measurements of salt concentrations are available near roads, the link between road maintenance salting activities and observed concentrations of salt in ambient air is yet to be quantified. In this study the NORTRIP road dust emission model, which estimates the emissions of both dust and salt from the road surface, is applied at five sites in four Nordic countries for ten separate winter periods where daily mean ambient air measurements of salt concentrations are available. The model is capable of reproducing many of the salt emission episodes, both in time and intensity, but also fails on other occasions. The observed mean concentration of salt in PM10, over all ten datasets, is 4.2 μg/m 3 and the modelled mean is 2.8 μg/m 3, giving a fractional bias of −0.38. The RMSE of the mean concentrations, over all 10 datasets, is 2.9 μg/m 3 with an average R 2 of 0.28. The mean concentration of salt is similar to the mean exhaust contribution during the winter periods of 2.6 μg/m 3 . The contribution of salt to the kerbside winter mean PM10 concentration is estimated to increase by 4.1 ± 3.4 μg/m 3 for every kg/m 2 of salt applied on the road surface during the winter season. Additional sensitivity studies showed that the accurate logging of salt applications is a prerequisite for predicting salt emissions, as well as good quality data on precipitation. It also highlights the need for more simultaneous measurements of salt loading together with ambient air concentrations to help improve model parameterisations of salt and moisture removal processes. Highlights: For the first time emissions of road salt have been modelled. The model successfully reproduces many of the observational datasets. Salt emissions in PM10, during winter, are as high as exhaust emissions. A relationship between road salt application and concentrations is presented.